The Baldovan Institution Abuse Inquiry: a forgotten scandal. Issue 3 (September 2019) - May, David
In this paper, I resurrect a long-forgotten inquiry into abuse and maladministration at an institution for people with learning disabilities, the Baldovan Institution near Dundee, that has lain buried in the archives for the past 60 years. I contrast the response to it with the very different response to the similar revelations of the Ely Hospital Inquiry more than a decade later. Whereas Ely opened up the institutional sector to greater public scrutiny and brought with it a formal commitment from the government to shift the balance of care away from the long-term hospital, Baldovan produced recommendations that were limited to the institution and had no impact on public policy or institutional practice. I consider the reasons for this and its implications.